Evaluation of Baryte Ores from Selected Sites in Obubra Mine of Cross River State, Nigeria, for Application as a Weighting Agent in Drilling Fluid: A Physical Characterization - Utibe Benedict Edem; Oji Akuma; Kuye, Ayoade; Ogbonna, Friday Joel (Journal of petroleum science and technology, 2024)
Baryte, a non-metallic mineral, is used primarily for the formulation of drilling mud to control reservoir pressure during drilling. However, despite its abundant reserves in Nigeria, the international oil companies (IOC) operating in Nigeria still apply imported baryte for operations. Therefore, in this research, the physical properties (specific gravity (SG), hardness and moisture content (MC, and pH)), of baryte deposits from 5 selected sites in Obubra mine of Cross River State, were determined and compared, vis-à-vis the API specifications, to ascertain their suitability for use in oil drilling. The white powder obtained from a streak test on the 5 ores indicated that all were indeed baryte ores. Furthermore, the samples were separately washed, dried, crushed, ground, and milled. In addition, the ore’s hardness of 3.5, and MC range of 0.00-0.01%, and pH range of 7-7.4, were all within the API specifications. Moreover, readings from the SG obtained were; site 1=4.25, site 2 = 4.28, site 3 = 4.32, site 4 = 4.12 and site 5 = 3.37. Thus, baryte in sites 3 and 5 recorded the highest and lowest SG, respectively. Ultimately, these results showed that ores from sites 1, 2, and 3 meet the API 4.20 specification for drilling purposes. At a SG of 4.12, site 4 sample, fell slightly below 4.20, while site 5 sample was unsuitable for drilling. Therefore, baryte from sites 4 and 5 should be further processed to meet the API SG specification for drilling. These findings prove that Obubra baryte possesses crucial criteria for drilling mud formulation.